MANAJEMEN DAN STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM PELAKSANAAN PROGRAM PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH - Herdianto Wahyu Pratomo; Thoriq, Thoriq; Nurhaemin, Nurhaemin; Dian Dinarni; Yansri, Alifianita Anake (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the management and leadership strategies of school principals in the implementation of the Merdeka Curriculum program, specifically the Program Penguatan Profil Pelajar Pancasila (P5) or the Strengthening of Pancasila Student Profile program. The research utilizes a literature review with five main stages: topic determination, database source search, database selection, analysis and synthesis, and conclusion drawing. The results of the literature review indicate that in order to successfully implement the Merdeka Curriculum, particularly the P5 project, several leadership and management strategies from school principals are necessary. The management and leadership strategies consist of three key components: leadership adaptability, collaborative leadership, and leadership that emphasizes the integration of Pancasila values into the school culture.